Mariae Vitae kongregacijos misionieriška veikla - Keidošiūtė, Elena (Lietuvos istorijos studijos, 2009)
The research of Jewish conversions and their concepts in Vilnius city and Vilnius bishopric is aimed at the activity of congregation Mariae Vitae (1737-1864) - unique both in Lithuania and in Europe at large. According to the rule of Mariae Vitae Congregation, it had to deal with religious and lay education of converted girls (mainly Jewish) and provide them with practical skills of work so they could establish in Catholic society. The innovatory social program of Mariae Vitae Congregation, including education and financial help, answered to possible problems of neophytes in Poland and Lithuania of the 18th-19th centuries. There was no institution dedicated to the care of Jewish catechumens and Mariae Vitae Congregation filled that gap, relieving the integration to Catholic society. The Jews themselves opposed this practice and tried to regain lost members of the community, but these attempts could be successful only if a neophyte was already an adult and showed a will to come back. Besides honest will to baptize, widowhood, potential marriage with a Catholic, and financial problems could be very real spurs to turn to Mariae Vitae sisters.